Silicon Fertilization Improves Physiological Responses in Sugarcane Cultivars Grown Under Water Deficit - de Camargo, M. S.; Bezerra, B. K.L. [UNESP]; Holanda, L. A. [UNESP]; Oliveira, A. L.; Vitti, A. C.; Silva, M. A. [UNESP] (Springer Nature, 2019)
There are few results about association Si and water deficit in sugarcane plants, regarding physiological aspects. The objective of this study was to investigate the effects of Si fertilization and water deficit imposed during two seasons on sugarcane cultivars using physiological evaluations, biomass measurements, and determination of the Si content in the plants and soil. Two experiments were conducted in a randomized block design: four sugarcane cultivars (drought-tolerant: RB86-7515 and SP83-2847; drought-sensitive: RB85-5536 and RB85-5453), two levels of Si (0 and 600 kg ha−1 Si), and with and without water deficit during spring (October 2014) or winter (July 2015). Si fertilization increased soluble Si in the soil in both experiments. Si provided increases in relative water content (RWC) for RB85-5536 and SP83-2847, in carotenoids content for RB85-5453 and SP83-2847, and dry weight (DW), water potential (Ψw), and SPAD for RB86-7515 during spring under drought. During winter, Si improved RWC, Ψw, DW, and Si uptake and decreased electrolyte leakage in leaves. In conclusion, Si can be considered a feasible alternative to alleviate water deficit damage imposed in both studied seasons through different physiological alterations according to each cultivar.
Keywords: Drought; Plant nutrition; Silicate; Soil